2014
DOI: 10.1021/om5006116
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Reactivity of Ruthenium Complexes Bearing Arsenic-Containing Arsenic-Nitrogen-Arsenic-Type Pincer Ligand

Abstract: Dinuclear and mononuclear ruthenium complexes bearing an arsenic-containing arsenic-nitrogen-arsenic (ANA)-type pincer ligand are designed, prepared, and characterized by X-ray analyses. Both ruthenium complexes work as effective catalysts toward dehydrogenative transformations of alcohols.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 65 publications
0
10
0
Order By: Relevance
“…3 A well-designed arsenic−nitrogen−arsenic pincer-type ligand exhibits high catalytic selectivity in the dehydrogenative transformation of benzyl alcohol and benzylamine to form N-benzylidenebenzylamine. 4 Considering these pioneering works, it is rational that arsenic ligands would play pivotal roles in the further development of transition-metal catalysts. However, there are few easily accessible arsenic ligands despite the unique catalytic systems.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 A well-designed arsenic−nitrogen−arsenic pincer-type ligand exhibits high catalytic selectivity in the dehydrogenative transformation of benzyl alcohol and benzylamine to form N-benzylidenebenzylamine. 4 Considering these pioneering works, it is rational that arsenic ligands would play pivotal roles in the further development of transition-metal catalysts. However, there are few easily accessible arsenic ligands despite the unique catalytic systems.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Arsenic ligands, in general, possess higher oxidation tolerance in air, more massive steric hindrance, and poorer σ donation compared with phosphorus ones . The characteristic nature of arsenic ligands has so far exhibited some advantages such as high selectivity and reactivity in transition-metal-catalyzed reactions. In 1991, for example, Farina and Krishnan reported reaction rate acceleration in Stille cross-coupling with triphenylarsine (AsPh 3 ) . More recently, a palladium-catalyzed copper-free Sonogashira cross-coupling reaction with AsPh 3 has been developed .…”
Section: Introductionmentioning
confidence: 99%
“…[4] Nishibayashi and coworkers developed a ruthenium catalyst bearing an arsenic-nitrogen-arsenic pincer ligand, which gives different reaction selectivity from that with the phosphorus analogue due to the large atomic size of the arsenic atom. [5] Our group also found that arsole derivatives have superior air-stability and electrochemical reversibility to the phosphole analogues, though their photophysical properties are quite similar. [6,7] Particularly in the field of coordination chemistry, there are several papers on combination of phosphines and arsines.…”
Section: Introductionmentioning
confidence: 98%
“…It is known that a trivalent phosphorus atom has higher Lewis basicity than arsenic one in reference to aminophosphines and aminoarsines; the former formed more stable coordination to borane (BH 3 ) than the latter [4] . Nishibayashi and coworkers developed a ruthenium catalyst bearing an arsenic‐nitrogen‐arsenic pincer ligand, which gives different reaction selectivity from that with the phosphorus analogue due to the large atomic size of the arsenic atom [5] . Our group also found that arsole derivatives have superior air‐stability and electrochemical reversibility to the phosphole analogues, though their photophysical properties are quite similar [6,7]…”
Section: Introductionmentioning
confidence: 99%
“…With the novel ruthenium complexes bearing PCP ligands in hand, we carried out catalytic formation of an imine from the reaction of benzylamine with benzyl alcohol, following the previous reaction conditions by Milstein 4c and our group. 15 The reaction of benzylamine with 1 equiv of benzyl alcohol in the presence of 0.4 mol % of 2a and sodium isopropoxide (NaO i Pr) in toluene at a reflux temperature for 48 h gave Nbenzylidenebenzylamine in 86% yield (Table 2, run 1). The use of 2b as a catalyst under the same reaction conditions gave the same imine in 70% yield (Table 2, run 2).…”
Section: ■ Introductionmentioning
confidence: 99%